Lviv’s Banknotes in the Period of the Russian Occupation During the First World War - Orłyk, Switłana; Kocur, Wiktor; Szweć, Wołodymyr (Acta Archaeologica Lodziensia, 2020)
Lviv banknotes during the Russian occupation in the First World War. The article sets out the peculiarities of monetary circulation in the territory of the city of Lviv during its occupation by Russian troops during the First World War. Attention is drawn to the problems of introducing Russian rubles into monetary circulation throughout the occupied territories of Galicia formerly belonging to the Austro-Hungarian Empire. It is noted that the simultaneous existence of the currencies of the two empires in monetary circulation, and the absence of fractional money, complicated the settlement process, and contributed to the emergence of social and economic problems, which subsequently led to the necessity of issuing city bonds in Lviv. In response to the problems caused by the “fractional money crisis”, the Russian occupation authorities promoted, answering on the proposition of the Lvov government, the issuance of Lviv bonds with a face value of 1 crown (issued in September 1914). The difficult financial situation Lviv found itself in necessitated the further issue of city bonds with a face value of 100 crowns (issued in February 1915). The problems surrounding the issue of Lviv bonds by the Russian authorities during the occupation has been reconstructed on the basis of archival documents.